The integration of morphological design and topology optimization to enhance the visual quality of electricity pylons - Di Angelo, Luca; Furferi, Rocco; Gherardini, Francesco; Guardiani, Emanuele (Frontiers in Mechanical Engineering, 2022)
This paper proposes a systematic design method for artificial above-ground structures, like pylons, masts, and towers of infrastructures and facilities. This digital manufacturing-based approach considers the conventional requirements, such as regulatory and industrial feasibility, and those arising from social components to enhance the visual quality of the landscape where these structures will be installed. The method can achieve the structures' functional and aesthetic goals based on the application of computer-aided tools. In particular, this is achieved according to three key steps: • Morphological development of landscape-related symbolism, environment, or culture and social needs. • Topology optimization of the design concept, to reduce the structural weight and its visual impact. • Engineering of the resulting optimized structure. As a case study, the method is used for designing electricity pylons for the coastal territory of a Mediterranean European country, such as Italy. Citizens were involved during the identification phase of a symbolic shape for the concept development and during the final assessment phase. The result is a structure with enhanced visual quality according to international guidelines and fully complying with regulatory, safety, feasibility, and social requirements.